Further studying the Dirac field in FLRW space - Dhungel, Prem Raj; Sharma, Sanat Kumar; Khanal, Uday Raj (Scientific World, 2022)
Behaviour of the Dirac field in FLRW space is further investigated extending the previous work. WKB approximation up to the third order was used to solve the temporal part of the Dirac’s equation and hence the energy and particle current have been calculated to further details.